Factors Associated With Burnout During Emergency Medicine Residency. (September 2014) - Kimo Takayesu, James; Ramoska, Edward A.; Clark, Ted R.; Hansoti, Bhakti; Dougherty, Joseph; Freeman, Will; Weaver, Kevin R.; Chang, Yuchiao; Gross, Eric; Yarris, Lalena
Abstract Objectives While the prevalence of burnout in practicing emergency physicians has been studied, little is known of the prevalence and risk factors in emergency medicine (EM) residents. The aim of this study was to assess the prevalence of burnout among EM residents and the individual‐level factors associated with burnout. Methods Eight EM residency programs were surveyed using the Maslach Burnout Inventory (MBI). Demographic data and data on job satisfaction and tolerance of uncertainty in clinical decision‐making were collected using validated instruments. Results Of 289 eligible residents, 218 completed the MBI (response rate = 75%). A total of 142 residents (65%) met the criteria for burnout. Complete data sets of the other instruments were obtained from 193 (response rate = 67%), and this group comprised our study population. Subjects having a significant other or spouse had a higher prevalence of burnout compared to single residents (60% vs. 40%, p = 0.002). Poor global job satisfaction (p < 0.0001), lack of administrative autonomy (p = 0.021), and lack of clinical autonomy (p = 0.031) correlated with burnout, as did intolerance of uncertainty (p = 0.015). Conclusions Burnout is highly prevalent in EM residents. Interventions should be targeted at 1) improving resident autonomy in the emergency department where possible, 2) supervision and instruction on medical decision‐making that may affect or teach individuals to cope with risk tolerance, and 3) social supports to reduce work–home conflicts during training.